Thin-walled single and multi-cell CFRP composite tubes in uniform torsion–Local shear and distortional-torsional instability - Loughlan, J.; Yidris, N. B. (Elsevier, 2025)
The buckling performance of thin-walled single and multi-cell CFRP composite tubes in uniform torsion is examined in this paper using both the finite strip and finite element methods of analysis. Due consideration is given in the paper to the influence on performance of flexural anisotropy or the bend-twist coupling characteristics of the composite material. The paper highlights the importance of realising the significance of the applied torque direction on buckling performance. Markedly different stability levels are shown to be in existence for the clockwise and anticlockwise torsional loading cases of the thin-walled multi-cell CFRP composite tubes. This situation is, of course, not realised in isotropic metal construction or in specially orthotropic CFRP composite construction since such material systems are devoid of the effects of material flexural anisotropy and thus the significance of the applied torque direction in this case is no longer appropriate.